2019
DOI: 10.1016/j.enconman.2019.04.055
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of a concentrated photovoltaic-thermoelectric system with and without flat plate heat pipe

Abstract: Thermal management of photovoltaic cells is an essential research objective for increasing the conversion efficiency of the photovoltaic. Flat plate heat pipe is a passive cooling device capable of effectively reducing the solar cell temperature. Therefore, this study presents a numerical investigation of a hybrid photovoltaic-thermoelectric system with and without a flat plate heat pipe. A detailed comparative analysis of the electrical performance of the photovoltaic only, photovoltaic-thermoelectric and pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 147 publications
(45 citation statements)
references
References 42 publications
(43 reference statements)
0
45
0
Order By: Relevance
“…Photovoltaic (PV) Area [28] Glass thickness [31] EVA thickness [31] Polycrystalline silicon thickness [31] TPT thickness [31] Thermoelectric generator (TEG) i The table layout displayed in this section is not how it will appear in the final version. The representation below is solely purposed for providing corrections to the table.…”
Section: Base Value Referencementioning
confidence: 99%
See 1 more Smart Citation
“…Photovoltaic (PV) Area [28] Glass thickness [31] EVA thickness [31] Polycrystalline silicon thickness [31] TPT thickness [31] Thermoelectric generator (TEG) i The table layout displayed in this section is not how it will appear in the final version. The representation below is solely purposed for providing corrections to the table.…”
Section: Base Value Referencementioning
confidence: 99%
“…Temperature distribution in the layers of the photovoltaic are obtained using the three-dimensional energy equation below [28,29]:…”
Section: Photovoltaic Modelmentioning
confidence: 99%
“…A 3‐D model of a hybrid PV‐TEG system was developed in Shittu et al, where each of the subsystem was modeled separately before fully integrating the model.…”
Section: Hybrid Pv‐tegmentioning
confidence: 99%
“…An example of PV‐TEG study where passive cooling methods (such as heat pipe and PCM) are used can be seen in a few literatures discussed as follows. Shittu et al compared the performance of a PV‐TEG system with flat plate heat pipe and without heat pipe. They developed a 3‐D model of the system using finite element method and employed COMSOL software in solving the governing equations.…”
Section: Comparative Assessment Of Integrated Pv‐teg Devicesmentioning
confidence: 99%
“…However, the cost of traditional pair arrangement PV‐TE module is usually expensive, since TE has the appreciable higher expense and lower efficiency compared with the PV . Shittu et al revealed a PV‐TE system employing the flat plate microchannel heat pipe (MCHP) and then used the finite element method in the numerical simulation of the three dimensions to indicate the advantages of the new system, but in this simulation, the cold side temperature was set as a constant. Li et al took the test on the output characteristic of the novel PV‐TE device.…”
Section: Introductionmentioning
confidence: 99%